2012
DOI: 10.1038/onc.2012.241
|View full text |Cite
|
Sign up to set email alerts
|

ZRF1 controls oncogene-induced senescence through the INK4-ARF locus

Abstract: The reactivation of the INK4-ARF locus, which is epigenetically repressed by Polycomb proteins in healthy cells, is a hallmark of senescence. One mechanism of reactivating Polycomb-silenced genes is mediated by the epigenetic factor ZRF1, which associates with ubiquitinated histone H2A. We show that cells undergoing senescence following oncogenic Ras expression have increased ZRF1 levels, and that this binds to the p15INK4b, ARF and p16INK4a promoters. Furthermore, ZRF1 depletion in oncogenic Rasexpressing cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Each experiment was repeated twice. The primer sequences for ZRF1 amplification were 5′ C G C T C T G A C C T C T G C C T C T A 3 ′ a n d 5 ′ CAGAAGCATTTCTGTTTCTCCT 3′ [25]. GAPDH was used as an internal control and primer sequence were 5′ T G T T G C C AT C A AT G A C C C C T T C 3 ′ a n d 5 ′ CTCCACGACGTACTCAGCGC 3′.…”
Section: Real-time Pcr Analysesmentioning
confidence: 99%
“…Each experiment was repeated twice. The primer sequences for ZRF1 amplification were 5′ C G C T C T G A C C T C T G C C T C T A 3 ′ a n d 5 ′ CAGAAGCATTTCTGTTTCTCCT 3′ [25]. GAPDH was used as an internal control and primer sequence were 5′ T G T T G C C AT C A AT G A C C C C T T C 3 ′ a n d 5 ′ CTCCACGACGTACTCAGCGC 3′.…”
Section: Real-time Pcr Analysesmentioning
confidence: 99%
“…RAC also binds to ribosomes and is required for the interaction of Ssb with nascent chains (39)(40)(41). RAC/Ssb is connected to diverse cellular functions, including cotranslational folding (38,42,43), translational fidelity (44,45), and transcriptional regulation (46)(47)(48)(49). Recently, we found that RAC/Ssb also plays a role in the quality control of nonstop proteins and of model proteins that possess a bona fide stop codon but contain a C-terminal polylysine segment (termed polylysine proteins) (32).…”
mentioning
confidence: 99%
“…In this regard, our data suggest that, by developing strategies to recruit Zrf1 to chromatin and sustain its transcriptional effect, Zrf1 is a potential target for regenerative medicine. As Zrf1 has been shown previously to be involved in oncogene-induced senescence (Ribeiro et al 2013) and misregulated in several human tumors (Shoji et al 1995;Resto et al 2000;Greiner et al 2003), we suggest that Zrf1 could also play a role in brain tumor development. How Zrf1 is recruited to chromatin and, once there, specifically regulates different processes (senescence, specification of NPCs, NPC maintenance, and differentiation) remains to be addressed.…”
Section: Discussionmentioning
confidence: 91%